The Effectiveness of The Role Playing Technique to Train The Student's Speaking Ability of Grade IX of SMP Plus Al-Ishlah - Wahyuni Abtiyasari; Khoirul Wafa; Moh. Zainuddin; Wahyuni Abtiyasari; Khoirul Wafa; Moh. Zainuddin (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
The researcher intended to use the Role-play approach due to the low English speaking ability of class IX students at SMP Plus Al-Ishlah. The purpose of this study is to collect empirical data on the usefulness of the role-playing approach in training their speaking abilities. This research used a quantitative method and was conducted in two different class groups, namely the experimental and control classes with a quasi-experimental design. The researcher conducted the study during four meetings the first for the pre-test, the second and third for the treatment using Role Play technique, and the fourth for the post-test. The theory from Role Play according to (Shabani, 2010) is Zone of Proximal Development (ZPD) is a concept from the work refers to the range of tasks that a learner can perform with the help of a more knowledgeable individual. The t-test results show a T count value of (6.48) with a T table of (2.021) with a df of 45 students and a significance level of 0.05 or 90%. It indicates Ha is approved because